Governance, Intellectual Capital, and Sharia Compliance in Islamic Bank Profitability: Evidence from Indonesian Islamic Commercial Banks - Inul Indah Agustina; Dahlifah Dahlifah; Maya Mustika; Preztika Ayu Ardheta (Research of Islamic Economics, 2026)
This study examines the effects of Islamic Corporate Governance (ICG), Intellectual Capital (IC), and Sharia Compliance (SC) on the profitability of Islamic Commercial Banks in Indonesia during 2022–2024. Profitability is measured using Return on Assets (ROA). A quantitative approach with panel data regression analysis was applied to 36 firm-year observations from 12 Islamic Commercial Banks selected through purposive sampling. Model selection and classical assumption tests were conducted to ensure robust estimation. The results show that ICG, IC, and SC jointly have a significant effect on profitability. Partially, Intellectual Capital has a positive and significant effect on ROA, indicating that effective utilization of knowledge-based resources enhances financial performance. Islamic Corporate Governance also has a positive coefficient, although its significance is relatively weak, suggesting that its impact depends on the quality of governance implementation. Meanwhile, Sharia Compliance has a negative but statistically insignificant effect on profitability, implying that greater compliance does not necessarily generate short-term financial benefits. Overall, Intellectual Capital is the strongest determinant of profitability. These findings emphasize the importance of investing in human capital, organizational learning, and digital innovation while maintaining effective governance and adherence to Sharia principles to support sustainable long-term performance